BOARD STRUCTURE AND EARNINGS MANAGEMENT: EVIDENCE OF SOUTH EAST ASIA COUNTRIES CATEGORISED BY AGENCY COST LEVEL - Andi Manggala Putra; Hermita Arif (Faculty of Economics and Business, Hasanuddin University, 2017)
Agency theory infers that investors will incur cost to make alignment on principal-agent interest. A critic, however, has pointed out that the conflict of interest between principal and agent is not the only cause for agency cost. Cultural context (Johnson & Droege, 2004) and legal system (La Porta, et al., 2000) are also found as contributing factors. This study is to empirically investigate how board size, board independency, audit committee size and audit committee independency affect the earnings quality in the context of low or high level agency cost country according to Transparency International’s corruption level and Hofstede’s cultural values. 538 firm-year across 6 South East Asian countries (Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam) are observed in this research. Five Different accrual models (Jones, 1991; Dechow, Sloan, & Sweeney, Detecting Earnings Management, 1995; Kasznik, 1999; Dechow, Richardson, & Tuna, Earnings management and costs to investors from firms meeting or slightly exceeding benchmarks, 2002; Dechow & Dichev, The Quality of Accruals and Earnings: The Role of Accrual Estimation Errors, 2002) are used to generate abnormal accruals which will be used as proxy for earnings management while to generate suitable factors from corporate governance variables, principal component analysis (PCA) is employed. Results indicate that (1) earnings management is efficient; (2) size and independency of Board of Director and audit committee are effective in reducing earnings management behaviour; (3) the management of firms operating in higher agency cost context will take advantage from the structure of corporate governance (size and independency of Board of Directors and audit committee) to conduct earnings management. Additionally, it is also found that bigger size (higher leverage) firms perform less (more) accounting discretion compared to their counterparts.